2021
DOI: 10.1016/j.amsu.2021.103104
|View full text |Cite
|
Sign up to set email alerts
|

Attitude toward refractive error surgery and other correction methods: A cross-sectional study

Abstract: Background Refractive errors are the most common vision problem and prove to be a significant health issue. There are several methods for correction of refractive errors including spectacles, contact lenses and refractive surgery. Nowadays, the reliance on contact lenses and glasses is decreased by means of refractive eye surgery. Our study aimed to determine the awareness of refractive surgery among undergraduate medical students and their preferred method of refractive error correction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 22 publications
3
8
0
Order By: Relevance
“…The cosmetic purpose and comfortable effect were the main reasons for state of comfortable using contact lenses. Our results were slightly similar to the results of previous study which showed that more than half of the students found glasses comfortable where the main reason was ease of use while the main cause for glasses discomfort was their limiting effect on daily activity, being not aesthetically pleasing and required more maintenance (Alhibshi et al, 2021). Moreover, another study done in Saudi Arabia showed that most of the participants believed that glasses are easily accessible and increased their quality of life (Alghamdi et al, 2019).…”
Section: 30%supporting
confidence: 90%
See 1 more Smart Citation
“…The cosmetic purpose and comfortable effect were the main reasons for state of comfortable using contact lenses. Our results were slightly similar to the results of previous study which showed that more than half of the students found glasses comfortable where the main reason was ease of use while the main cause for glasses discomfort was their limiting effect on daily activity, being not aesthetically pleasing and required more maintenance (Alhibshi et al, 2021). Moreover, another study done in Saudi Arabia showed that most of the participants believed that glasses are easily accessible and increased their quality of life (Alghamdi et al, 2019).…”
Section: 30%supporting
confidence: 90%
“…The prevalence of having refractive surgery reported in this study was similar to what reported by previous studies (Alghamdi et al, 2019;Alhibshi et al, 2021). The low rate of performing refractive surgeries among our population could be related to the high cost of the surgery where 42.9% of those participants reported not welling to undergo the operation reported the cost as the barrier for not performing the surgery as well as fear from complications and fear from need for spectacles after the surgery.…”
Section: 30%supporting
confidence: 87%
“…Compared to the results of the Saudi study, fear of complications was the most reason preventing them from undergoing surgery. [4] It is interesting that the majority of students considered that the complications from this surgery were minor (50.5%) and not serious.…”
Section: Discussionmentioning
confidence: 97%
“…However, about 38.4% of the students in our study were willing to undergo corneal refractive surgery which is similar to the study in India at 36.6%, and less than the rate of readiness of undergraduate students in Saudi Arabia for the surgery at 69.5%. [4] Those who did not nd themselves ready to undergo refractive surgery stated that the main obstacle was the lack of information about the procedure (39%). These ndings herald a gap in knowledge about corneal refractive surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery is a familiar treatment for myopia, but it has certain requirements for patients' conditions. Some patients may have sequelae such as dry eye, keratitis or vision regression after operation [5]. Orthokeratology is an effective way of delaying the development of myopia [6].…”
Section: Introductionmentioning
confidence: 99%